Correlation between uniaxial compressive strength (UCS) and blasting geometry on rock excavation at PT Agincourt Resources. (December 2018) - Nainggolan, D R; Sitorus, R; Eveny, O N; Sariandi, F
Abstract: To achieve the set objectives, an analysis of uniaxial compressive strength and blasting geometry was used in five different rock types. Blasting is categorized successfully if the blasted material size distribution is ≤45 cm above 85%. With twenty-two times of blasting in five rock types, analyzed fragmentation distributions <45 cm in size. The result of analysis obtained by type of BPM 16.5 MPa with pf 0.64 kg/m 3 and drill pattern dimension is 16.34 m 2 has distribution of fragmentation 94.44%; SBPM 70.5 MPa with pf 0.92 kg/m 3 and drill pattern dimension is 11.85 m 2 has distribution of fragmentation is 92.47%; VAN 81.6 MPa with pf 0.96 kg/m3 and drill pattern dimension is 9.45 m 2 has distribution of fragmentation 88.65%, VANh 51.1 MPa with pf 0.86 kg/m 3 and drill pattern dimension is 12.54 m 2 has distribution of fragmentation 86.32% and VBX 74.0 MPa with pf 0.94 kg/m 3 and drill pattern dimension is 12.19 m 2 has distribution of fragmentation is 86.31%. The blasting result for all rock types was distributed above 85%. From the correlation of measured variables, it was observed that there is a good correlation between blasting geometry and uniaxial compressive strength. It was observed that blasting geometry increases with decrease in uniaxial compressive strength and an increase in blasting geometry will decrease the powder factor.